2021
DOI: 10.3390/ani11030700
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Genetic Diversity of Protist Parasites in Captive Non-Human Primates, Zookeepers, and Free-Living Sympatric Rats in the Córdoba Zoo Conservation Centre, Southern Spain

Abstract: Little information is currently available on the epidemiology of parasitic and commensal protist species in captive non-human primates (NHP) and their zoonotic potential. This study investigates the occurrence, molecular diversity, and potential transmission dynamics of parasitic and commensal protist species in a zoological garden in southern Spain. The prevalence and genotypes of the main enteric protist species were investigated in faecal samples from NHP (n = 51), zookeepers (n = 19) and free-living rats (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 69 publications
5
47
4
Order By: Relevance
“…has been found in 15.4% (67/432) of captive animals in a zoo in Southern Spain [ 52 ], in 23.6% (232/984) of birds in an ornithological garden in the same region [ 53 ], and in non-human primates (NHP) at the Barcelona Zoo at an unspecified carriage rate [ 54 ]. A higher prevalence rate of 45.1% (23/51) was reported by PCR and Sanger sequencing methods in NHP from the Córdoba Zoo Conservation Centre in Southern Spain [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…has been found in 15.4% (67/432) of captive animals in a zoo in Southern Spain [ 52 ], in 23.6% (232/984) of birds in an ornithological garden in the same region [ 53 ], and in non-human primates (NHP) at the Barcelona Zoo at an unspecified carriage rate [ 54 ]. A higher prevalence rate of 45.1% (23/51) was reported by PCR and Sanger sequencing methods in NHP from the Córdoba Zoo Conservation Centre in Southern Spain [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding animal hosts, Blastocystis STs have been found in faecal samples from Iberian pigs (ST1, ST3, and ST5) and wild boars (ST5) living sympatrically [ 30 ]. A high genetic variability including ST1, ST2, ST4, ST7, and ST14 was observed in different wild carnivore species in different regions of the country [ 58 ], whereas ST1, ST3, and ST8 were reported as circulating in captive NHP [ 32 ]. Most Blastocystis STs described in Spanish animal populations were potentially zoonotic, particularly ST1–ST5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten subtypes have been reported in humans, ST1–ST9 and ST12, with most studies reporting primarily ST1–ST4 [ 17 ]. The subtypes reported in humans have also been observed in animals indicating that these subtypes may have zoonotic potential [ 18 , 19 , 20 , 21 , 22 ]. For example, the identification of ST6, a subtype mostly identified in avian species, in slaughterhouse staff members provided evidence of the potential zoonotic transmission of this subtype through direct contact between chickens and their handlers [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…and the ciliates Balantioides coli and Troglodytella abrassarti are also a common finding in the faeces of captive NHP ( Johnson-Delaney, 2009 ; Medkour et al, 2020 ; Helenbrook and Whipps, 2021 ). All the above-mentioned protist species have been documented in NHP collections of zoological gardens and sanctuaries in Asian ( Mul et al, 2007 ; Nath et al, 2012 ; Du et al, 2015 ; Adrus et al, 2019 Zhao et al, 2020 ), African ( Munene et al, 1998 ; Pomajbíková et al, 2010a , b ; Li et al, 2011 ; Mbaya and Udendeye, 2011 ; Ryan et al, 2012 ; Adetunji, 2014 ; Debenham et al, 2015 ; Kouassi et al, 2015 ), American ( Phillips et al, 2004 ; Wenz et al, 2010 ; Milozzi et al, 2012 ; da Silva Barbosa et al, 2015 ), and European ( Levecke et al, 2007 ; Berrilli et al, 2011 ; Köster et al, 2021a ) countries. These studies revealed marked differences in occurrence rates depending on host species, geographical location, and detection method used.…”
Section: Introductionmentioning
confidence: 99%